2019
DOI: 10.1186/s12864-019-5564-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution population structure and runs of homozygosity reveal the genetic architecture of complex traits in the Lipizzan horse

Abstract: Background The sample ascertainment bias due to complex population structures remains a major challenge in genome-wide investigations of complex traits. In this study we derived the high-resolution population structure and levels of autozygosity of 377 Lipizzan horses originating from five different European stud farms utilizing the SNP genotype information of the high density 700 k Affymetrix Axiom™ Equine genotyping array. Scanning the genome for overlapping runs of homozygosity (ROH) shared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Number of ROHs could reflect the type of breeding program. Small local and imported conserved populations bred inter se had a greater (>20) number of ROHs (e.g., BMF, BB, BL, RW1 and C), meaning a reduced genetic diversity similar to what was shown in small livestock populations kept by individual breeders or in local breeds [ 2 , 27 , 28 , 29 , 30 , 31 ]. In contrast, the genomes of two- and three-breed F 1 crossbred progenies contained a lesser (<6) number of ROHs ( Table 1 ; Figure 1 ), which was consistent with lower ROH metrics observed in other studies on crossbred animals (e.g., [ 3 , 32 ]).…”
Section: Resultsmentioning
confidence: 92%
“…Number of ROHs could reflect the type of breeding program. Small local and imported conserved populations bred inter se had a greater (>20) number of ROHs (e.g., BMF, BB, BL, RW1 and C), meaning a reduced genetic diversity similar to what was shown in small livestock populations kept by individual breeders or in local breeds [ 2 , 27 , 28 , 29 , 30 , 31 ]. In contrast, the genomes of two- and three-breed F 1 crossbred progenies contained a lesser (<6) number of ROHs ( Table 1 ; Figure 1 ), which was consistent with lower ROH metrics observed in other studies on crossbred animals (e.g., [ 3 , 32 ]).…”
Section: Resultsmentioning
confidence: 92%
“…The spc computes such a network using an algorithm requiring the specification of the maximum number of nearest neighbours (k-NN) that an individual can have. A k-NN = 10 was set as the default value, as suggested by previous applications [43][44][45].…”
Section: Investigation Of Population Structure Using Genomic Informationmentioning
confidence: 99%
“…Similar results reported for Austrian Noriker horse Grilz-Seger et al (2019a) that identified overall seven ROH islands shared by more than 50% of the entire analysed sample. The high frequency of ROH islands on ECA11 was also found in genome of Lipizan horse (Grilz-Seger et al, 2019b).…”
Section: Resultsmentioning
confidence: 54%